MULTI-CRITERIA VALIDATION OF A PRECIPITATION-RUNOFF MODEL - Beldring S. (My University, 2002)
The multi-criteria calibration procedure MOCOM-UA was used to evaluate the validity of a physically based precipitation-runoff model by forcing the model to simulate several observed system responses simultaneously. The model is based on kinematic wave approximations to saturated subsurface flow and saturation overland flow at the hillslope scale in a landcape with a shallow layer of permeable deposits overlying a relatively impermeable bedrock. The following results were found; (i) the MOCOM-UA method was capable of exploiting information about the physical system contained in the measurement data time series; (ii) the multi-criteria calibration procedure provided estimates of the uncertainty associated with model predictions and parameters; (iii) multi-criteria calibration constraining the behavior of the precipitation-runoff model to observed runoff and groundwater levels reduced the uncertainty of model predictions; (iv) the multi-criteria method reduced the uncertainty of the estimates of model parameters; (v) the precipitation-runoff model was able to reproduce several observed system responses simultaneously during both calibration and validation periods; and (vi) the groundwater table depths exerted a major control on the hydrological response of the investigated catchment.
Keywords: PRECIPITATION-RUNOFF MODEL; GROUNDWATER; TILL DEPOSITS; PARAMETER ESTIMATION; MULTIPLE OBJECTIVES